2002
DOI: 10.1177/104345420201900305
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty, Anxiety, and Symptoms of Posttraumatic Stress in Parents of Children Recently Diagnosed with Cancer

Abstract: The purpose of the study was to describe relationships between uncertainty, anxiety, and symptoms of posttraumatic stress (PTS) in parents of children recently diagnosed with cancer. The study was guided by the Uncertainty in Illness Theory. The setting was a children's hospital. Participants were 15 parents of 12 children recently diagnosed with cancer. Anxiety was measured by the State-Trait Anxiety Inventory. Uncertainty was measured by the Parent Perception of Uncertainty Scale. Symptoms of PTS were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 20 publications
2
63
2
6
Order By: Relevance
“…These findings are consistent with previous studies indicating an inverse association between psychological distress and illness-related knowledge [16,17]. It is found that amongst key problems faced by parents whose children are affected by cancer include uncertainty, which is associated with anxiety and post-traumatic stress symptoms [28]. Parents often become uncertain about the controllability of cancer and the complexity of information related to illness and treatments.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with previous studies indicating an inverse association between psychological distress and illness-related knowledge [16,17]. It is found that amongst key problems faced by parents whose children are affected by cancer include uncertainty, which is associated with anxiety and post-traumatic stress symptoms [28]. Parents often become uncertain about the controllability of cancer and the complexity of information related to illness and treatments.…”
Section: Discussionsupporting
confidence: 82%
“…As the experience cancer influences the emotional response of parents in relation to their child's needs, the ability of the child or adolescent to deal with adverse situations is related to the parents' ability to manage situations of crises. This relationship reinforces the importance of understanding the psychosocial impact of childhood cancer on parents (Hoekstra-Weebers et al, 2001;Robinson, Gerhardt, Vannatta, & Noll, 2007;Santacroce, 2002;Streisand, Kazak, & Tercyak, 2003).…”
Section: The Psychosocial Impact Of Childhood Cancer On Parentsmentioning
confidence: 92%
“…About half of parents report moderate to intense levels of posttraumatic stress, including intrusive thoughts, treatment avoidance, physiological responses, flashbacks and psychological agitation (Kazak, Boeving, Alderfer, Hwang, & Reilly, 2005;Santacroce, 2002;Vrijmoet-Wiersma et al, 2008). On the other hand, the work of Jurbergs, Long, Ticona e Phipps (2009) does not report significant differences in posttraumatic stress symptoms between parents of children undergoing treatment and symptoms in parents of healthy children.…”
Section: Psychosocial Distressmentioning
confidence: 96%
See 1 more Smart Citation
“…children diagnosed with cancer who scored high on levels of uncertainty were at an increased risk for anxiety and posttraumatic stress disorder [Santacroce, 2002]. However, some parents have reported that personal growth can be a positive outcome of uncertainty by recognizing that an uncertain outcome leaves open the possibilities for a positive outcome for their child [Cohen, 1993;Clarke-Steffen, 1993a;Rosenthal et al, 2001].…”
Section: Introductionmentioning
confidence: 99%